A2.21 The increase of circulating CD4+ T-cells with effector phenotype in patients with systemic lupus erythematosus may be reverted after belimumab therapy. (24th February 2016) - Piantoni, S; Scarsi, M; Andreoli, L; Dall'Ara, F; Zanola, A; Tincani, A; Airò, P
Abstract : Background and objectives: T-cell activation may be one of the pathogenic mechanisms of systemic lupus erythematosus (SLE). After repeated antigenic stimulation, T-cells undergo different modifications, leading to the differentiation into effector memory T-cells (CCR7-CD45RA-) and highly experienced memory T-cells (CCR7-CD45RA+). Similarly, down-modulation of CD28 may lead to the expansion of the CD28-T-cells, a subpopulation with peculiar effector activities. Recent studies showed that memory CD4 + T-cells are increased in the peripheral blood of SLE patients, whereas contradictory data are reported on CD28-T-cells. Belimumab is an anti-Blys therapy approved for SLE. The aims of this study were the characterisation of T-cell phenotype in a cohort of patients with SLE, according with disease activity, and the analysis of T-cell phenotype modifications after 6 months of therapy with belimumab. Materials and methods: Phenotypic analysis of peripheral blood T lymphocytes was made by flow-cytometry. First, a cross-sectional study on 41 consecutive SLE patients was performed. Second, 7 patients treated with belimumab were longitudinally followed. Disease activity was evaluated by SLEDAI-2K score. Results: SLE patients were divided in two groups according disease activity: patients with SLEDAI-2K ≥6 (n.6) had a higher percentage of circulating CD4 + T-cells with CD28- phenotype (11 vs 2.5%, p = 0.01), as well as of those with an effector memory (34 vs 18%, p = 0.03), or highly experienced memory (8 vs 1%, p = 0.01) phenotype, in comparison with patients with low disease activity (n.35). After 6 months of treatment with belimumab, a trend toward a reduction of the CD4 + CD28- T-cells was observed (from 10.5% to 4.6%; p:0.12). In particular, a reduction of CD4 + CD28- T-cells showing an effector memory phenotype (from 31.6 to 26% of CD4 + CD28- cells, p = 0.01) was found. Conclusions: CD4 + T-cells subpopulations displaying phenotype characteristics of effector lymphocytes are proportionally expanded in patients with active SLE, but some of these abnormalities seems to be reverted by anti-BlyS therapy. Since the presence of BlyS receptor 3 on T cells and of a BLyS-dependent T-cell activation pathway have been well demonstrated, further studies are warranted to understand the possible effects of anti-BlyS therapy on T cells from SLE patients.